2018
DOI: 10.1111/ecog.03506
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of reef fish assemblages in tropical Oceanic islands

Abstract: Diversity patterns are determined by biogeographic, energetic, and anthropogenic factors, yet few studies have combined them into a large‐scale framework in order to decouple and compare their relative effects on fish faunas. Using an empirical dataset derived from 1527 underwater visual censuses (UVC) at 18 oceanic islands (five different marine provinces), we determined the relative influence of such factors on reef fish species richness, functional dispersion, density and biomass estimated from each UVC uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 50 publications
(110 reference statements)
1
44
1
Order By: Relevance
“…Additionally, oceanic systems receive very little sediment input from continental landmasses and, as such, conserve clear waters that are adequate for the feeding activity of these planktivores fishes (Johansen & Jones, 2013). As a result, most oceanic islands are dominated by reef planktivores, despite differences in fishing pressure (e.g., Friedlander et al, 2010;Krajewski & Floeter, 2011;Luiz et al, 2015;Quimbayo et al, 2017;Quimbayo et al, 2018). Our results, showing both a pivotal role of wave exposure in shaping reef fish assemblages and a numerical and biomass dominance of planktivores at São Tomé Island are consistent with this scenario.…”
Section: Reef Fish Assemblagesmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, oceanic systems receive very little sediment input from continental landmasses and, as such, conserve clear waters that are adequate for the feeding activity of these planktivores fishes (Johansen & Jones, 2013). As a result, most oceanic islands are dominated by reef planktivores, despite differences in fishing pressure (e.g., Friedlander et al, 2010;Krajewski & Floeter, 2011;Luiz et al, 2015;Quimbayo et al, 2017;Quimbayo et al, 2018). Our results, showing both a pivotal role of wave exposure in shaping reef fish assemblages and a numerical and biomass dominance of planktivores at São Tomé Island are consistent with this scenario.…”
Section: Reef Fish Assemblagesmentioning
confidence: 99%
“…In the last 15 years, studies focused on oceanic islands have revealed remarkable features, such as unusual high fish biomass and peculiar benthic communities (e.g., Sandin et al, 2008;Stevenson et al, 2007;Williams et al, 2013;Quimbayo et al, 2018). The high abundance and biomass of large predators and herbivorous species in these isolated systems contrasts with more accessible reef systems (Friedlander et al, 2003(Friedlander et al, , 2010Graham & McClanahan, 2013;Morais, Ferreira, & Floeter, 2017;Williams et al, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Oceanic islands are often considered natural laboratories, where anthropogenic effects on native communities are absent or less pronounced than on continents (Sandin et al ., ; Quimbayo et al ., ). Features such as distance from the mainland and island size and age can affect colonisation and extinction rates on oceanic islands, driving patterns of richness and endemism in marine communities (Hachich et al ., ; Pinheiro et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…The increase in the depth range of scientific exploration is contributing to a better understanding of the distribution of the world's marine biodiversity and accelerating the rate of knowledge acquisition about the distributions and biogeographical patterns of marine organisms. For instance, despite being considered a cosmopolitan species, there were few records for the chondrichthyan Odontaspis ferox (Risso, 1810) in the southwestern (Fergusson et al, 2008;Graham et al, 2016;Long et al, 2014) Despite the isolation and small area of SPSPA, the richness of the fish species is similar to that recorded for other larger islands of the SA (Pinheiro et al, 2015;Quimbayo et al, 2019;Soto, 2001) and MAR (Wirtz et al, 2017), and should keep increasing with further studies, based on the species accumulation curves and low overlap between adults and larvae records ( Figure 5). This relatively high fish richness level recorded for SPSPA is a consequence of extensive sampling on Thus, it is believed that additional deep exploration and sampling effort in SPSPA might reveal more endemic and undescribed deep-sea species.…”
Section: Discussionmentioning
confidence: 91%